Sequencing and analyzing complete mitochondrial genome of Anser cygnoides (Anserini: Anserinae) - Mu-Yeong Lee; Hey Sook Jeon; Yu-Seong Choi; Sungbae Joo; Junghwa An (Mitochondrial DNA. Part B. Resources, 2017)
The complete mitogenome sequence of Anser cygnoides was determined and compared with those previously released. The whole mitogenome was 16,740 bp, with 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and 1 putative non-coding region (1178 bp). The overall nucleotide composition was 30.2%, 32.0%, 15.1%, and 22.7% for A, C, G, and T, respectively. Phylogenetic analyses strongly supported two clades in Anserini and demonstrated that A. cygnoides is not monophylogenetic. This division of A. cygnoides indicates that more research is necessary to clarify phylogenetic relationships for A. cygnoides and determine how they relate to morphological traits.